Kinerja Infrastruktur Pendukung Disabilitas di DKI Jakarta - Raflis; Irfan Amrullah; Syarif Hidayatullah (Jurnal TESLINK : Teknik Sipil dan Lingkungan, 2025)
The provision of disability-friendly infrastructure in Jakarta faces several challenges, such asthe improperly installed guiding blocks and ramps, which hinder the mobility of people withdisabilities and increase the risk of accidents. This study aims to evaluate the performance ofdisability infrastructure and provide solutions to create a more inclusive and safer city. Usingboth quantitative and qualitative methods, data was collected through interviews, surveys, andfield observations at Jatinegara Station, Jakarta, with 14 respondents, including visuallyimpaired individuals and policymakers. The analysis shows that both the users of disabilityfacilities and policymakers lack sufficient understanding of disability infrastructure, as seen fromthe misalignment between the facilities and the proper design standards. This hinders themobility of people with disabilities, particularly the visually impaired. As a solution, the studyrecommends adding support facilities, such as specialized training for transportation staff andplacing staff at key locations, as well as supporting facilities like tactile maps and audio signageto help visually impaired individuals navigate public transport more easily and safely.